Valorization of Beet-Processing Sugar Factory by-Products for in-situ Gluconic Acid Production by using Aspergillus Niger Fermentation - Kelleci, Kubra; Altundogan, H. Soner; Tanyildizi, M. Saban (Springer India, 2023)
The beet-processing sugar industry is facing a severe crisis in some countries due to high production costs. This situation also negatively affects the beet producers. To increase the profit of beet-processing sugar plants, it is considered that the evaluation of by-products such as molasses, beet-pulp, and carbonation cake to obtain valuable organic acids could be commercially available. In this study, gluconic acid production by fermentation with A. niger has been investigated by using by-products obtained from beet-processing sugar plant. The experimental conditions have been optimized for gluconic acid production by submerged, semi solid-state, and solid-state fermentation routes by using Response Surface Methodology (RSM). Gluconic acid production efficiencies under the optimized conditions for submerged, semi solid-state, and solid-state fermentations were calculated as 0.258, 0.354, and 0.262 g gluconic acid per g of absolute solid substrate, respectively. It has been determined that citric and oxalic acid together with gluconic acid could be produced at the significant levels for all three fermentation routes. It has been observed that obtaining oxalic and citric acid along with gluconic acid using A. niger depend strongly on pH. Gluconic acid was produced at near-neutral pH, whereas oxalic (pH similar to 4-4.5) and citric (pH < 2) acids were obtained at lower pH. In conclusion, in-situ production of gluconic and important organic acids can be realized by using beet-processing sugar plant byproducts and some waste energy with simple fermentation techniques. Under the present circumstances, this approach is the most convenient way to survive the crisis that uses appropriate fungal/bacterial cultures.
Keywords: Gluconic acid; Sugar beet pulp; Molasses; Fermentation; A. niger; Response surface methodology